Collision avoidance algorithm and validation based on V2P at intersection - Jiabo ZHANG; Chaofan WANG; Zhe LI (Dianxin kexue)
Traffic accidents have risen in recent years,especially in the case of traffic accidents without signal intersection.A pedestrian and vehicle prevailing game model was established based on the delay and the risk payoff of the pedestrian and the vehicle at the intersection,which could give pedestrians and vehicles a reasonable priority prevailing decision.Moreover,an improved game model was established on the basis of the introduction of the driver’s reward and fine payoff.Practices proved that the improved model could increase the pass rate of pedestrian,which was more conducive to road traffic safety.In addition,the traditional virus transmission model was improved to analyze the psychology of traffic participants,which proved the necessity of illegal punishment by numerical simulation.The research provides a theoretical reference for the future development of pedestrian and vehicle collision avoidance system.